Розширення функціональності полімерних композитних матеріалів - Girchenko, A. G.; Gorelov, B. M.; Malashenkov, S. P.; Mischenko, V. N.; Starokadomskiy, D. L.; Shevlyakov, Yu. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
The prospects for enhancement of functional possibilities of polymer composites on the base of polyester, urea formaldehyde, and epoxy resins filled with silica and titanium oxide particles due to variation of concentration, size, and specific surface area of particles have been analyzed. The variation effects of the сhemical nature of reinforcing filaments, inorganic compounds on improvement of mechanical properties, thermal and chemical stability of composites and reducing the evolution of toxic compounds have been investigated.